2021
DOI: 10.1515/jpem-2021-0033
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of hypertension and elevated blood pressure and its correlation with overweight/obesity among students aged 6–17 years in Suzhou

Abstract: Objectives Lifestyle changes have led to an increase in the prevalence of hypertension in Chinese children and adolescents. The aim of this study was to analyze the prevalence of hypertension and its association with overweight and obesity among students aged 6–17 years in Suzhou. This retrospective analysis included physical examination data of primary and junior high school students in Suzhou Industrial Park from 2016 to 2019. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
4
0
3
Order By: Relevance
“…Currently, there are not many reports on the prevalence of high blood pressure among Chinese students. Chen et al [ 16 ] reported a prevalence of high blood pressure of 9.92% among students aged 6 to 17 years in Suzhou. Li et al [ 17 ] reported a prevalence of 12.26% of high blood pressure among students under 18 years old in Lanzhou.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are not many reports on the prevalence of high blood pressure among Chinese students. Chen et al [ 16 ] reported a prevalence of high blood pressure of 9.92% among students aged 6 to 17 years in Suzhou. Li et al [ 17 ] reported a prevalence of 12.26% of high blood pressure among students under 18 years old in Lanzhou.…”
Section: Discussionmentioning
confidence: 99%
“…Snížení prevalence obezity je prevencí PHT/HT. (17) Recentní studie adolescentů s PHT vyšetřených pomocí ABPM ukázala ve srovnání s kontrolní skupinou zvýšený srdeční minutový volum a tepový objem. Tyto údaje se nelišily od adolescentů s již prokázanou HT, a to i při srovnání periferní cévní rezistence a centrálního systolického tlaku u PHT, resp.…”
Section: Mimo Prenatálního Existuje I Postnatální Programmingunclassified
“…The prevalence of childhood overweight and obesity increased at an alarming rate over the past decades in China ( 1 ) . Childhood overweight and obesity is correlated with elevated blood pressure (BP) ( 2 ) and other chronic disease ( 3 ) . Apart from the recognised physiological results, depression ( 4 ) , anxiety ( 4 ) and low self-esteem ( 5 ) might also result from obesity.…”
mentioning
confidence: 99%